ANALISIS PENGARUH PENGGUNAAN AIR DENGAN PH < 7 PADA CAMPURAN BETON NORMAL TERHADAP KUAT TEKAN - Suryanto; Albert (Jurnal Informasi, Perkebunan dan Sipil, 2021)
In general, the water used for making concrete is water with a pH of 7, as well as the standard testing in the Lab, but in reality sometimes the work of making concrete in the field does not pay attention to the pH of the water used, such as the use of swamp water or well water made around the project site. The use of concrete structures that are in direct contact with sulfuric acid compounds will affect the quality of the compressive strength of concrete because sulfuric acid can corrode concrete. This study observes how much damage to the concrete if in the mixing and maintenance process using acid water with a pH level <7 and the effect on the compressive strength of concrete with curing duration of 3, 7, 14, and 28 days. The highest compressive strength of concrete at a design age of 28 days is 240,196 Kg/cm² or 19,237 MPa using acid water in a concrete mixture using Conch brand cement, followed by Gresik cement at 18,167 MPa, Tiga Roda cement at 16,837 MPa and Holcim cement at 16,837 MPa.